ANALYSIS OF THE IMPLEMENTATION OF EMPLOYEE PERFORMANCE APPRAISAL AT BANKS IN BANTEN - Sucihati Sucihati; Cecep Warman; Eka Febrianata; Suharno Suharno (Jurnal Ekonomi, 2022)
This study aims to analyze the implementation of employee performance appraisal at the Bank in Banten. The type and approach of research is field research with a Qualitative approach. Data collection techniques are obtained from observation, interviews and documentation. Based on research and discussion, it can be concluded that the application of assessments to improve employee performance at banks in Banten has been carried out properly and the company's plan to determine employee performance is to prepare employees who are of good quality and also competent. The impact of employee performance appraisal there are both positive and negative. The positive impact is the emergence of better work motivation, clarity from the work standards that have been done, and reciprocity to past performance such as rewards, promotions. Meanwhile, the negative impact is being reprimanded by the boss, not getting rewards and being stopped.